STUDI KOMPARASI PENYELESAIAN SENGKETA PERCERAIAN MELALUI PENGADILAN DI INDONESIA DENGAN BRITANIA RAYA (INGGRIS DAN WALES): Comparative Study Of Divorce Settlement Through The Courts In Indonesia With The United Kingdom Of Britain (England And Wales) - Hasibuan, Winda Fitriani; Kirana, Gandes Candra (Faculty of Law, Universitas Trisakti, 2024)
Every marriage does not rule out the possibility of divorce, so divorce is not a new thing to be found in society. However, each region of the country has different laws for finalizing divorce, such as Indonesia and the UK. This research aims to describe the settlement of divorce according to the Indonesian legal system with the UK along with the advantages and disadvantages of the divorce settlement. This research was conducted normatively based on secondary data, and data analysis is done descriptively and conclusions were drawn using deductive methods. Based on the research conducted, what regulates the divorce process in Indonesia is carried out in accordance with the provisions of civil law that apply in public courts, namely HIR, RBg, Rv, the Marriage Law, and the Law on Religious Courts. Meanwhile, the divorce settlement process in the UK is carried out in accordance with The Family Procedure (Amendment) Rules Number 44 of 2022 and for Muslim couples it is regulated in The Muslim Law (Shariah) Council UK. England and Wales have not made peace and evidentiary efforts in examining and adjudicating divorce cases as Indonesia has done so far. So that this is a weakness of divorce settlements in the UK and advantages for divorce settlements in Indonesia.